2017
DOI: 10.1111/apa.14136
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing and addressing the link between mass media and the increase in obesity among European children: The European Academy of Paediatrics (EAP) and The European Childhood Obesity Group (ECOG) consensus statement

Abstract: Health policies in Europe must take account of the range of social media influences that promote the development of childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
2
27
0
3
Order By: Relevance
“…Additionally, food companies and retailers employ effective marketing strategies to influence purchasing habits, which can have impact on health. For example, there is strong evidence for a positive relationship between childhood obesity and exposure to food marketing (Mazur et al 2017). Competing in this crowded and commercialised environment are evidence-based government health promotion messages, front-and back-of-pack labelling systems, and portion size guides, which often fail to resonate with consumers (Persoskie et al 2017).…”
Section: Nutrition: the Contested Spacementioning
confidence: 99%
“…Additionally, food companies and retailers employ effective marketing strategies to influence purchasing habits, which can have impact on health. For example, there is strong evidence for a positive relationship between childhood obesity and exposure to food marketing (Mazur et al 2017). Competing in this crowded and commercialised environment are evidence-based government health promotion messages, front-and back-of-pack labelling systems, and portion size guides, which often fail to resonate with consumers (Persoskie et al 2017).…”
Section: Nutrition: the Contested Spacementioning
confidence: 99%
“…4 The growing amount of alarming scientific reports has led the European Academy of Paediatrics and the European Childhood Obesity Group to write a consensus statement targeting parents and other stakeholders. 5 Their main messages concern the negative influence of social media and TV on children's sleep and the consumption of unhealthy foods-both are also strong risk factors for obesity. When it comes to smartphones, their warning against overuse concerns the negative effects of advertising to children, but also the lack of face-to-face contact with peers, which may increase social problems and lead to mental ill-health.…”
Section: Smartphones-the Good the Bad And The Ugly Consequences Of Usementioning
confidence: 99%
“…A Canadian study including 5000 11‐ to 20‐year‐old students showed that greater use of social media was associated with shorter sleep duration in a dose‐response fashion . The growing amount of alarming scientific reports has led the European Academy of Paediatrics and the European Childhood Obesity Group to write a consensus statement targeting parents and other stakeholders . Their main messages concern the negative influence of social media and TV on children's sleep and the consumption of unhealthy foods—both are also strong risk factors for obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A task force from The European Academy of Paediatrics and the European Childhood Obesity Group found a strong link between obesity levels across European countries and childhood mass media exposure . They maintain that parents and society need to develop a better understanding of the influence of social media on dietary habits and on children's cognitive and physical development.…”
Section: Mass Media Is Linked To Increasing Obesity In European Childrenmentioning
confidence: 99%